Event-triggered adaptive predefined-time anti-unwinding attitude tracking control for spacecraft - Guogang Wang; Zichao Feng; Youyang Qu; Hongwei Sun (PLoS ONE, 2025)
This paper addresses the problem of predefined-time attitude tracking control for rigid spacecraft subject to external disturbances and unknown inertia parameters. First, a predefined-time non-singular sliding surface is designed to ensure that the closed-loop system converges within a predefined time. Second, to tackle the unwinding problem inherent in quaternion-based modeling, a potential function is introduced in the controller design to guarantee anti-unwinding performance even outside the sliding surface. The proposed controller not only suppresses chattering but also ensures both anti-unwinding behavior and predefined-time convergence. Then, an event-triggered mechanism is developed to reduce communication burden while avoiding Zeno behavior. The proposed control method can make the attitude tracking error converge to an arbitrary predefined residual set. Finally, simulation results verify the effectiveness of the proposed method.